2016
DOI: 10.1127/fal/2016/0839
|View full text |Cite
|
Sign up to set email alerts
|

Variation in functional trait composition of benthic invertebrates across depths and seasons in a subarctic lake

Abstract: Benthic invertebrate communities play a fundamental role in lake ecosystems, and the understanding of how those benthic communities are structured, particularly in terms of the identity and spatiotemporal distribution of their functional traits, is key to our understanding of how lake ecosystems work. In Takvatn, a subarctic lake in northern Norway, we identified the taxonomic and functional identity of the species characterizing benthic communities across three seasons and six different depths. Invertebrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The zooplankton community comprises ten rotifers, seven cladocerans and two copepods species (Dahl‐Hansen et al 1994, Primicerio and Klemetsen 1999, Amundsen et al 2009, 2013). The upper littoral benthos community has a richness of 25 macroinvertebrate taxa, composed of 18 insects and seven non‐insects (Klemetsen et al 1992, 2020, Klemetsen and Elliott 2010, Frainer et al 2016; see the Supporting information for more details on the zooplankton and benthic invertebrate community of Lake Takvatn). The current fish community comprises trout, charr and three‐spined stickleback Gasterosteus aculeatus .…”
Section: Methodsmentioning
confidence: 99%
“…The zooplankton community comprises ten rotifers, seven cladocerans and two copepods species (Dahl‐Hansen et al 1994, Primicerio and Klemetsen 1999, Amundsen et al 2009, 2013). The upper littoral benthos community has a richness of 25 macroinvertebrate taxa, composed of 18 insects and seven non‐insects (Klemetsen et al 1992, 2020, Klemetsen and Elliott 2010, Frainer et al 2016; see the Supporting information for more details on the zooplankton and benthic invertebrate community of Lake Takvatn). The current fish community comprises trout, charr and three‐spined stickleback Gasterosteus aculeatus .…”
Section: Methodsmentioning
confidence: 99%
“…Interannual variation in prey availability (i.e., temporal variations in prey communities) has frequently been observed in aquatic systems (e.g., Løvik and Kjellberg 2003;Hämäläinen et al 2003;Frainer et al 2016;Prati et al 2021), likely shaping foraging and diet composition of predators (e.g., Ringler 1985;Baudrot et al 2016). In the present study, even though most interannual variation observed with the singleand two-year time scales could be ascribed to bias from low sample sizes of certain ontogenetic stages, there were a few dietary changes that were consistent also for the five-and ten-year time scale approaches, supporting that these represent valid temporal variation.…”
Section: Discussionmentioning
confidence: 99%
“…Takvatn (69°07′N, 19°05′E) is a subarctic, oligotrophic, and dimictic lake in northern Norway that has been the focus of intensive ecological and food web studies for more than 30 years (details in Amundsen et al., 2009, 2013, 2019). The lake is situated 214 m above sea level with a surface area of 15 km 2 and a maximum depth of ca 80 m. There is little macrovegetation in the lake, but the littoral zone (3–10 m depth) has dense beds of the grass‐like macroalgae Nitella sp., which contain the highest abundances of G. lacustris (Frainer et al., 2016).…”
Section: Methodsmentioning
confidence: 99%